PANAI TRADITION STUDY IN VISUAL NARRATIVE PERSPECTIVE (CASE STUDY: FILM TARUNG SARONG) - Andini, Puang; Rahajaan, Jerry Dounald; Nugraha, Rika (Universitas Negeri Makassar, 2023)
The Panai tradition is a tradition in the wedding structure of the Makassar Bugis Tribe which entirely discusses the concept of ‘siri’ (self-esteem), this Panai tradition is also implemented in the film Tarung Sarong by Archie Hekagery produced by StarVision Plus in 2020 by choosing Netflix as the release media. So that a film review process is needed using theories (1) Qualitative (2) Visual Narrative (3) Ethnography (4) Ethics and Emic. Based on the results of the analysis, there was a shift between the Panai tradition in the film Tarung Sarung and those in the Bugis community of Makassar. In the past understanding in the Bugis community of Makassar, the Panai tradition was interpreted as the concept of self-esteem of a man who came to propose to a woman, while the current understanding of the Panai tradition is interpreted as the concept of ‘doi’ (money) given from the male side to the female side by looking at the female social strata including noble lineage, economic status. level of education, physical condition, and occupation.